VARIABILITY OF MANUAL AND COMPUTERIZED METHODS FOR MEASURING CORONAL VERTEBRAL INCLINATION IN COMPUTED TOMOGRAPHY IMAGES - Vrtovec, Tomaž; Pernuš, Franjo; Likar, Boštjan (Image Analysis and Stereology, 2015)
Objective measurement of coronal vertebral inclination (CVI) is of significant importance for evaluating spinal deformities in the coronal plane. The purpose of this study is to systematically analyze and compare manual and computerized measurements of CVI in cross-sectional and volumetric computed tomography (CT) images. Three observers independently measured CVI in 14 CT images of normal and 14 CT images of scoliotic vertebrae by using six manual and two computerized measurements. Manual measurements were obtained in coronal cross-sections by manually identifying the vertebral body corners, which served to measure CVI according to the superior and inferior tangents, left and right tangents, and mid-endplate and mid-wall lines. Computerized measurements were obtained in two dimensions (2D) and in three dimensions (3D) by manually initializing an automated method in vertebral centroids and then searching for the planes of maximal symmetry of vertebral anatomical structures. The mid-endplate lines were the most reproducible and reliable manual measurements (intra- and inter-observer variability of 0.7° and 1.2° standard deviation, SD, respectively). The computerized measurements in 3D were more reproducible and reliable (intra- and inter-observer variability of 0.5° and 0.7° SD, respectively), but were most consistent with the mid-wall lines (2.0° SD and 1.4° mean absolute difference). The manual CVI measurements based on mid-endplate lines and the computerized CVI measurements in 3D resulted in the lowest intra-observer and inter-observer variability, however, computerized CVI measurements reduce observer interaction.